1999
DOI: 10.1089/thy.1999.9.149
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Concentration of Interleukin-12 in Patients with Silent Thyroiditis and Graves' Disease

Abstract: We previously reported that interleukin-5 (IL-5), secreted from Th2 cells, was increased in patients with Graves' disease, but not in patients with silent thyroiditis. In this study, we investigated serum levels of interleukin-12 (IL-12) in order to examine the role of Th1-type immune response in the pathogenesis of autoimmune thyroid diseases. Serum levels of IL-12 were determined by a highly sensitive sandwich enzyme-linked immunosorbent assay in 68 patients with Hashimoto's thyroiditis (26 of whom had silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(16 reference statements)
1
16
1
Order By: Relevance
“…On the other hand, a recent study shows that adipose tissue secretion of interleukin-6 is elevated in Graves' disease (36) even after restoration of euthyroidism. Some authors have found elevated cytokine concentrations in autoimmune hypothyroidism (37,38), as opposed to our finding of decreased MBL levels. In parallel to our findings, it has been shown that serum sIL-2R levels are positively modulated by thyroid hormone, mostly independently of thyroid autoimmunity (39 -41).…”
Section: P-valuescontrasting
confidence: 99%
“…On the other hand, a recent study shows that adipose tissue secretion of interleukin-6 is elevated in Graves' disease (36) even after restoration of euthyroidism. Some authors have found elevated cytokine concentrations in autoimmune hypothyroidism (37,38), as opposed to our finding of decreased MBL levels. In parallel to our findings, it has been shown that serum sIL-2R levels are positively modulated by thyroid hormone, mostly independently of thyroid autoimmunity (39 -41).…”
Section: P-valuescontrasting
confidence: 99%
“…Such a result suggests a different immunological status for euthyroid and hypothyroid HT patients, and is in agreement with the experimental evidence demonstrating an important role of Th2 cytokines in the control of the Th1-mediated autoimmune process (1, 34 -36). The fact that our hypothyroid patients were on long-term L-thyroxine treatment suggests that the immunological abnormalities described could not be caused by impairment of thyroid function, as has been suggested previously (12). In this view, the peripheral lymphocytes might express specific markers reflecting the degree of organ involvement in HT.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the pharmacological stimulus allows the study of cytokines that are expressed at low levels, such as IL-4 (28). Cellular immune responses have been studied in circulating (6,12,18) and infiltrating lymphocytes (6 -10) of the patients with thyroid autoimmune disease. Since in the organ-specific diseases the reliable reflection of the autoimmune state lies in the target organ, the analysis of the intra-thyroid lymphocytes is probably the best way to investigate the immunological status in the patients with thyroid autoimmunity (30).…”
Section: Discussionmentioning
confidence: 99%
“…ported in patients with GD [21][22][23]. The increased expression of IL-12 mRNA in thyroid and orbital fat tissues has been reported in GD and in active GO, respectively [24,25].…”
Section: Discussionmentioning
confidence: 89%
“…IL-12 induces IL-2, IFN-γ and TNF-β from Th1 cells and IFN-γ from NK (natural killer) cells. Increased serum levels of IL-12 have been reported in GD [21][22][23]. Furthermore, IL-12B mRNA expression has been demonstrated in thyroid tissues from patients with GD [24] and in orbital fat tissues from patients with active GO [25], but not in extraocular muscle tissues (EOM), or EOM-derived T cell lines from patients with GO undergoing corrective strabismus surgery [26].…”
mentioning
confidence: 99%